Pembangunan komuniti di dalam perlaksanaan konsep bandar selamat; kajian kes : Bukit Jelutong, Seksyen U8, Shah Alam, Selangor Darul Ehsan. - Ali, Nor Eeda (2006)
In Malaysia, crime rate keep on increasing from time to time and has been a threat to the security and peaceful environment of the community. Department of Town and Country Planning had implemented Safe City concept as one of the ways to reduce crime. The concept of Safe City aims at creating a safe and peaceful environment of city and housing, so as to reduce crime rate through environmental design principles, security and community development. Therefore, the study is to identify some of the aspects of community development of the Safe City concept in the housing area in Bukit Jelutong, Section U8, Shah Alam. The total number of sample size are 100 houses with 90 percent confidence level. SPSS is used as a tool to analyze data. Questionnaires survey is conducted as to get information on community development in the study area such as resident profile, resident’s opinion on the safety level of housing, community level, level of community association the confidence level among community and their opinion to reduce crime. The study showed that the community development has reached a respective level in terms of reducing crime rate. Through the establishment of private community security, which is supervised by Bukit Jelutong Resident Association [BJRA] as to ensure the safety level in the housing area. The community have also proposed a few associations but they no longer active due to lack of support, lack of programs and also time constraints among community because they are preoccupied with their office work. The study also showed that 100 percent of respondents agreed that the contribution of community plays an important role to control the crime problem because they are the ‘eyes and ears’ to the security group. Two strategies are recommended so as to improve the current situation in the study area. First; is to consolidate associations which concern the safety aspect and social programs. So as to achieve the first strategy, the community development strategy is recommended which include education, towards the importance of community, community awareness, community initiative and sacrifices